8-Chloro-cAMP-Related Changes on Mice Uteri. (2002) - Actis, Andrea; Croci, Maximo; Levin, Emanuel; Bergoc, Rosa
Abstract : Histopathological effects of cAMP analog (8-Chloro-cAMP), tamoxifen, and medroxyprogesterone, alone or combined, upon BALB/c mice uteri are reported. 8-Chloro-cAMP diminished uterine weight, but did not modify its histopathology or estral cycle significantly. Tamoxifen diminished uterine weight showing cystic hyperplasia and an estral cycle arrested at diestrus. Medroxyprogesterone increased uterine weight, caused a swelling of the endometrium and a pseudopregnancy estrus. When combined with 8-Chloro-cAMP, tamoxifen or medroxyprogesterone always had a predominant effect. We concluded that the effects of 8-Chloro-cAMP on mice uteri did not cause significant changes on its histopathology, but diminished its weight.